2017
DOI: 10.4252/wjsc.v9.i8.107
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stromal cell in regenerative medicine: A review

Abstract: The application of appropriate cell origin for utilizing in regenerative medicine is the major issue. Various kinds of stem cells have been used for the tissue engineering and regenerative medicine. Such as, several stromal cells have been employed as treat option for regenerative medicine. For example, human bone marrow-derived stromal cells and adipose-derived stromal cells (ADSCs) are used in cell-based therapy. Data relating to the stem cell therapy and processes associated with ADSC has developed remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 116 publications
1
70
0
1
Order By: Relevance
“…Recently, adipose-derived stem cells (ASCs) have been demonstrated to be one of the main sources of MSCs (7)(8)(9)(10). Kato et al (11) have shown that allogeneic transplantation of an ASC combined with artificial skin can accelerate wound healing in Zucker diabetic fatty rats in vivo.…”
mentioning
confidence: 99%
“…Recently, adipose-derived stem cells (ASCs) have been demonstrated to be one of the main sources of MSCs (7)(8)(9)(10). Kato et al (11) have shown that allogeneic transplantation of an ASC combined with artificial skin can accelerate wound healing in Zucker diabetic fatty rats in vivo.…”
mentioning
confidence: 99%
“…Adipose-derived mesenchymal stem cells (ASCs) represent a population of self-renewing and multipotent cells that reside in the vascular stroma of adipose tissue; under specific conditions, they are capable of differentiating into cellular phenotypes that resemble adipocytes, myocytes, chondrocytes, and osteocytes (Patrikoski et al, 2019). This indigenous cell population is known to play a central role in embryologic development, tissue growth, tissue repair, and regeneration due to its pluripotency and immunomodulatory capacity (Scuderi et al, 2013;Dai et al, 2016;Tabatabaei Qomi and Sheykhhasan, 2017). However, its role in end-organ homeostasis and repair following organ damage remains largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that stem cell therapy can contribute to diabetic wounds and other diseases [4][5][6]. Compared with other types of stem cells, adipose-derived stem cells (ADSCs) have specific advantages and fewer limitations; they are abundant and easily harvested, can be delivered via a minimally invasive procedure, are associated with fewer ethical issues and have less risk of inducing tumorigenicity and the host immune response [7,8].…”
Section: Introductionmentioning
confidence: 99%